Entrepreneurial Ecosystem: Interaction between Government Policy, Funding and Networks (Study on Entrepreneurship in West Java) - Egidius Fkun; Muhammad Yusuf; Arief Yanto Rukmana; Zahra Fitriana Putri; M. Ade Kurnia Harahap (Westscience Press, 2023)
This study examines the entrepreneurial ecosystem in West Java, Indonesia, and explores the interaction between government policy, funding, and networks in shaping the ecosystem. The study uses a mixed-methods approach, including surveys and interviews with entrepreneurs and key regional stakeholders. The findings suggest that government policy, such as tax incentives and support for small and medium enterprises, is critical in creating a supportive environment for entrepreneurship in the region. Funding and networking opportunities were identified as essential components of the ecosystem. The study highlights the need for more investment-ready businesses and networking opportunities for entrepreneurs in the region. The study also identifies several challenges entrepreneurs face in the region,including limited access to funding and networking opportunities, and regulatory barriers. The study concludes that continued support for entrepreneurship in the region is necessary and suggests areas for future research, including the impact of specific government policies, cultural factors, and technology on the entrepreneurial ecosystem in West Java. Overall, this study provides valuable insights into the factors that shape the entrepreneurial ecosystem in West Java and has important implications for policymakers and stakeholders seeking to support entrepreneurship in the region.